Penentuan Awal Bulan Qamariah Menurut Al-Qur'an dan Sunnah (Analisis Terhadap Ormas dan Pemerintah) - Firdaus Firdaus; Amir Syarifuddin; Zulkarnaini Zulkarnaini (Jurnal Kajian dan Pengembangan Umat, 2022)
Determination of the beginning of the month of Qamariah is very necessary, this is related to worship, such as determining the period of iddah, haul zakat, fasting and other transactions. People become restless when the determination of the beginning of the month is different between Islamic organizations and the government. The image of Muslims becomes even worse in the eyes of non-Muslims when there is conflict. This study aims to reveal the causes of differences of opinion in determining the criteria for the beginning of the month, efforts to unite opinions, and unification of vision in determining the criteria for the beginning of the month of Qamariah. The research method used is a literature study with a descriptive analysis approach. Data collection on the procedure for determining the beginning of the month of Qamariah started from the time of the Prophet Muhammad who adhered to rukyat. The results showed that the difference in determining the criteria for the beginning of the month of Qamariah was due to the way to understand the arguments about the rukyat and reckoning methods. Unification can be done by holding muzakarah, training and deliberation every year at the isbat session. The Hisab Rukat Agency (BHR) of the Ministry of Religion of the Republic of Indonesia determines the criteria for the beginning of the month using the Ru'yah Imkan method, which is to see the height of the new moon at least two degrees above the horizon at sunset. Unifying the vision for the commonality of each mass organization by holding training, seminars, involving BMKG and LAPAN. At its peak, an isbat meeting was held that nationally the beginning of Ramadan, Shawwal and Eid al-Adha was determined. Alternative unification of ru'yah and astronomical calculations, by seeing directly using the senses of sight and science so that an astronomical view enters by looking at the calculations hinted at in the Qur'an Surah al-Baqgarah verse 189, Arrahman verse 5, Yunus verse 5, Yasin verse 39 and at-Taubah verse 36.Keywords: Qamariyah month, reckoning rukyat, determination